Fibrinolytic Activity and the Effects of Beta-Pyridylcarbinol (Ronicol) in Patients with Arteriosclerosis Obliterans - Grodzińska, L; Basista, M; Kȩdzior, A; Korbut, R; Kostka-Trąbka, E; Gryglewski, R (Thrombosis and Haemostasis, 1983)
Twenty-one patients with arteriosclerosis obliterans of lower extremities were treated with beta-pyridylcarbinol (Ronicol) for five weeks. The long-term therapy with beta-pyridylcarbinol did not influence platelet aggregability. Activation of the fibrinolytic system was observed. This fibrinolytic effect of Ronicol was abolished in patients treated with aspirin. In most cases a slight clinical improvement was seen, manifested by elongation of pain-free walking distance and increased blood flow in affected limbs. It is concluded that the therapeutic effect of Ronicol in humans may be partly mediated by the release of endogenous prostacyclin.
Keywords: Arteriosclerosis obliterans; Platelet aggregation; Fibrinolysis; Aspirin